ANALYSIS OF THE RELATIONSHIP OF BRAND AWARENESS AND BRAND TRUST WITH BRAND LOYALTY IN MEN'S CARE PRODUCTS - Seseli, Eka Merdekawati; Kusuma, Rr. Chusnu Syarifa Diah; Sarwani, Sarwani (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
This research aims to analyze the relationship between brand awareness, brand trust, and brand loyalty in men's care products. Using a quantitative approach, data was collected from a sample of men's grooming product consumers through an online survey totaling 160 respondents determined using a convenience sampling approach. Data analysis uses the SPSS application by displaying the results of data processing through testing research instruments with validity and reliability tests, multiple regression analysis, coefficient of determination, and hypothesis testing. The results of the analysis show that there is a significant relationship between the level of brand awareness and brand trust and the level of brand loyalty. These findings highlight the importance of increasing consumer awareness and trust in men's grooming brands to strengthen brand loyalty. The practical implications of this research emphasize the importance of effective marketing strategies to build and maintain brand awareness and brand trust, increase consumer loyalty, and maintain brand position in a competitive market. This research makes a significant contribution to our understanding of the dynamics of the relationship between brand awareness, brand trust, and brand loyalty in the context of men's grooming products, and provides a foundation for further research in this domain.